2014
DOI: 10.1186/s12918-014-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

KeyPathwayMiner 4.0: condition-specific pathway analysis by combining multiple omics studies and networks with Cytoscape

Abstract: BackgroundOver the last decade network enrichment analysis has become popular in computational systems biology to elucidate aberrant network modules. Traditionally, these approaches focus on combining gene expression data with protein-protein interaction (PPI) networks. Nowadays, the so-called omics technologies allow for inclusion of many more data sets, e.g. protein phosphorylation or epigenetic modifications. This creates a need for analysis methods that can combine these various sources of data to obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 15 publications
0
69
0
Order By: Relevance
“…Here we defined minimal networks that best represent the clustered phospho-signal using subnetwork extraction procedures (Alcaraz et al, 2014). For each of the 16 kinases, we extracted minimal subnetworks that contained all phospho-proteins and on average 12% connecting, non-phosphorylated proteins from a global yeast interactome of 5,804 proteins and 63,545 PPIs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here we defined minimal networks that best represent the clustered phospho-signal using subnetwork extraction procedures (Alcaraz et al, 2014). For each of the 16 kinases, we extracted minimal subnetworks that contained all phospho-proteins and on average 12% connecting, non-phosphorylated proteins from a global yeast interactome of 5,804 proteins and 63,545 PPIs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several related algorithms that search networks to retrieve active subnetworks have been developed in the context of expression analysis (Alcaraz et al, 2014), disease associations (Vanunu et al, 2010) and cancer mutational analysis (Hofree et al, 2013;Creixell et al, 2015b). We overlaid the phosphorylation values on the corresponding proteins in the yeast interactome network as seeding points to search for subnetworks with a maximum number of phospho-proteins.…”
Section: Network Inference Analyses Of Py-sites Of the Yeast Model Sumentioning
confidence: 99%
See 2 more Smart Citations
“…Many other studies have also focused on developing methods for identifying aberrant network modules and pathways by utilizing molecular networks and other omics data. For example, Alcaraz et al [120] developed KeyPathwayMiner, a method for extraction of aberrant network modules from PPI network by integrating gene expression and DNA methylation data. The authors demonstrated the performance of KeyPathwayMiner on TCGA colorectal cancer patients.…”
Section: Computational Methods For Disease Sub-typing and Bio-marker mentioning
confidence: 99%